Cultural Preservation and Architectural Evolution: The Impact of Tourism on Bale Banjar in Kuta Bali - Mitha Mahastuti; Arya Bagus Mahadwijati Wijaatmaja; Ni Wayan Ardiarani Utami (Architectural Research Journal, 2025)
This article explores the relationship between tourism and cultural preservation as well as the evolution of bale banjar architecture in Kuta, Bali. In the context of increasing tourist visits, this study analyzes both the positive and negative impacts on traditional architectural structures and local cultural practices. The expansion of the tourism industry in Kuta has had a significant impact on local culture and traditional architecture, particularly on the bale banjar, which generally serves as a symbol of community gathering for the local adat. The study broadly aims to examine how tourism influences cultural preservation and the evolution of bale banjar architecture. The methods used include qualitative analysis through interviews with local residents, direct observations, and literature reviews. The findings reveal that tourism drives changes in the design of bale banjar to attract visitors, but it also poses risks to traditional values. On the one hand, increased attention to local culture has the potential to strengthen preservation efforts, but on the other hand, commercialization can undermine the authenticity of the architecture. These findings highlight the need for sustainable tourism management strategies to maintain a balance between economic development and cultural preservation in Kuta, Bali.